STRATEGI KOMUNIKASI PEMASARAN EVENT ORGANIZER SUMATERA SATU DALAM MEMPERTAHANKAN LOYALITAS KLIEN DI PEKANBARU - Zulfandi "; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Business competition in Indonesia is currently experiencing very rapid progress. This is proven by the mushrooming of various forms of business entities engaged in goods and services, both small and large scale. One human need is the need for an event or event organizer. Event organizers are now increasingly needed by the public. One of the big event organizers in Pekanbaru is Sumatra One. Pekanbaru is a city that has high potential in business opportunities so that many event organizers have sprung up and become competitors from Sumatra one. Although the presence of many new event organizers came Sumatra one can still maintain its clients from their standing until now. Therefore, researchers are interested in conducting research to find out the marketing communication strategies of Sumatra One in maintaining client loyalty in Pekanbaru.This study uses qualitative methods, namely the collection of data obtained based on the reality of the data in the field through observation, interviews, and documentation of the research subjects are 2 Sumatran One people and 2 loyal Sumatran clients selected using a purposive technique. To analyze the results of this study using interactive data analysis techniques, while the technique of checking the validity of the data through extended participation, increased perseverance, and triangulation.The results of this study indicate that the marketing communication strategy of Sumatra One in maintaining client loyalty in Pekanbaru by using two strategies focused by them, the first is personal selling which includes steps such as finding customers or qualifications, approaches, presentations, overcoming objections, follow-up or maintenance. While the steps of Sumatra one in direct marketing are direct email and telemarketing.